Real qualitative behavior of a fourth-order family of iterative methods by using the convergence plane - Magreñán, Á. Alberto; Cordero, Alicia; Gutiérrez, José M; Torregrosa, Juan Ramón (Mathematics and Computers in Simulation, 2017)
The real dynamics of a family of fourth-order iterative methods is studied when it is applied on quadratic polynomials. A Scaling Theorem is obtained and the conjugacy classes are analyzed. The convergence plane is used to obtain the same kind of information as from the parameter space, and even more, in complex dynamics. (C) 2014 IMACS. Published by Elsevier B.V. All rights reserved.
Keywords: real dynamics; nonlinear problems; convergence plane; basins of attraction; stability; JCR; Scopus